Are light traps baited with kairomones effective in the capture of Lutzomyia longipalpis and Lutzomyia intermedia? An evaluation of synthetic human odor as an attractant for phlebotomine sand flies (Diptera: Psychodidae: Phlebotominae) - Andrade, Andrey J.; Andrade, Mateus R.; Dias, Edelberto S.; Pinto, Mara C. [UNESP]; Eiras, Álvaro E. (Instituto Oswaldo Cruz, Ministério da Saúde, 2008)
Phlebotomine sand flies are often captured with human bait and/or light traps, either with or without an animal bait. More recently, synthetic attractants have been used as bait in traps to improve the capture of phlebotomine sand flies as well as other insects of medical and veterinary importance. The aim of the present study was to evaluate the effects of the kairomone 1-octen-3-ol (octenol) and the synthetic human odor BG-Mesh LureTM (BGML - lactic acid, caproic acid and ammonia) baited in modified CDC light traps on the capture of phlebotomine sand flies. The experiments followed the 5x5 Latin square design. Among the species caught, Lutzomyia intermedia apparently presented a dose-dependent response to octenol. The response obtained with the BGML, alone or in combination with octenol (5 mg/h), indicated some degree of attractiveness of these baits to different phlebotomine sand fly species. Octenol seems to be more attractive to L. intermedia than to Lutzomyia longipalpis, while the BGML presented a higher success in capturing L. longipalpis. When the components of the BGML were used separately, there was no increase in catching the female of L. intermedia. Apparently, there was no synergistic effect between the octenol and the BGML. In conclusion, the octenol and the BGML were demonstrated to be possible baits to attract some phlebotomine sand fly species.
Keywords: kairomones; octenol; BG-Mesh LureTM; Lutzomyia intermedia; Lutzomyia longipalpis; CDC light trap